1975
DOI: 10.1136/thx.30.4.405
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem assessment of chronic airways obstruction by tantalum bronchography.

Abstract: Thorax, 30,[405][406][407][408][409][410][411][412][413][414]. Postmortem assessment of chronic airways obstruction by tantalum bronchography. Tantalum bronchography was performed on 22 left lungs obtained at necropsy. Seven were from patients dying in cor pulmonale as a result of chronic airways obstruction and 15 were from unselected necropsies. Of the latter group, nine had no evidence of respiratory disease and six had pathological changes of emphysema and bronchial mucous gland enlargement when the lungs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Those subjects with Ն 25% emphysema had signi fi cantly lower TAC and generational airway counts than those subjects with , 25% emphysema. This fi nding is in agreement with an early study by Scott and Steiner, 29 which reported a decrease in macroscopic airway count by bronchography with tantalum in subjects with a high emphysema per centage measured by histologic means compared with those with a low emphysema percentage. Later, Montaudon et al 8 reported that there were no differences in the total and generational airway counts visible on CT scans between smokers and nonsmokers with normal lung function.…”
Section: Tac-emphysema Associationsupporting
confidence: 92%
“…Those subjects with Ն 25% emphysema had signi fi cantly lower TAC and generational airway counts than those subjects with , 25% emphysema. This fi nding is in agreement with an early study by Scott and Steiner, 29 which reported a decrease in macroscopic airway count by bronchography with tantalum in subjects with a high emphysema per centage measured by histologic means compared with those with a low emphysema percentage. Later, Montaudon et al 8 reported that there were no differences in the total and generational airway counts visible on CT scans between smokers and nonsmokers with normal lung function.…”
Section: Tac-emphysema Associationsupporting
confidence: 92%
“…In addition, roentogenographic examination of the airways using the conventional liquid contrast media has several disadvantages including poor aerosolization efficiency and potential short residence times (Díaz-López et al, 2010; Fischer and Blaug, 1969; Nadel et al, 1968). More promising results have been obtained by inhalation of powdered contrast media (mostly tantalum) (Nadel et al, 1968; Nadel et al, 1970; Scott and Steiner, 1975); however, these formulations were not pursued because of the difficulty in administration (Lafitte et al, 1982; Strecker et al, 1979), high cost, and lack of approval by the FDA (Flower and Armstrong, 1986; Gamsu and Nadel, 1972). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies of airways have taken a more direct approach, using techniques that demonstrate relationships between branches in the airway system. These techniques include the use of resin casts of the airways, and images of the airway system following injection of radio-opaque media or derived from serial section reconstruction (Hansen et al, 1975;Horsfield and Cumming, 1968;Horsfield et al, 1966;Kitagawa et al, 1971;Parker et al, 1971;Scott and Steiner, 1975). However, these methods can be time-consuming, lack required detail, or destroy the surrounding tissues (thus identification of the airway generation can not be combined with analysis of tissue components of the airway structure).…”
mentioning
confidence: 99%